Urgency of Farmer Participation in Livestock Value Chain Development in Indonesia - Guntoro, Budi (2016)
Small scale livestock farmers may also be legitimate part of the supply chain. They may be seen as producers of live animals and products that will distribute quality products through many actors in supply chain to end customers. The majority of small farmers in Indonesia raise animas for sale, Even in the most remote areas, many small farmers are connected to markets, selling small amounts of animals or products in a local village market or to a trader. The farmers many sell surplus that they cannot consume themselves. This paper discuses about current condition of livestock development. How farmer participated in development, market oriented, and value chain